2000
DOI: 10.1163/156851500750096345
|View full text |Cite
|
Sign up to set email alerts
|

Shame and Prophecy: Approaches Past and Present

Abstract: Shame is widely discussed both in the literature of psychology (in contradistinction to guilt) and social anthropology (in binary opposition with honour, where it is associated particularly with women and public loss of status). Recently, the honour–shame model has been used as heuristic pattern for analysing biblical texts. The focus has been primarily on the patriarchal narratives and Deuteronomistic history; yet the preponderance of shame vocabulary occurs in the prophetic corpus. Here the model proves to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…They would damage their community's honour if they committed a sin. Stiebert's (2000) opinion revealed that shame is widely discussed in both the psychological literature (as opposed to guilt) and social anthropology (its relation to honour is associated primarily with women and the loss of public status).…”
Section: Shame On Societymentioning
confidence: 99%
“…They would damage their community's honour if they committed a sin. Stiebert's (2000) opinion revealed that shame is widely discussed in both the psychological literature (as opposed to guilt) and social anthropology (its relation to honour is associated primarily with women and the loss of public status).…”
Section: Shame On Societymentioning
confidence: 99%
“…Leung Lai 2004) or what biblical metaphors are meant to connote or to evoke in their readers. Shame is an example of an emotional and social biblical phenomenon that could benefit from this kind of integrative research (e.g., Bechtel 1991; Stiebert 2000; 2002; Haddox 2011; Moon 2015; Hadjiev 2016; cf. Kollareth, Fernandez-Dols, and Russell 2018).…”
Section: Metaphor Studies and The Hebrew Bible Since 1980mentioning
confidence: 99%